Bacteria in the ECHAM5-HAM global climate model - Petrus, Ana; Lohmann, Ulrike; Storelvmo, Trude (Copernicus, 2011)
Bacteria are the most active naturally occuring ice nuclei (IN) due to the ice nucleationactive proteins on their surface, which serve as active sites for ice nucleation. Theirpotential impact on clouds and precipitation is not well known and needs to be inves-tigated. Bacteria as a new aerosol species were introduced into the global climate model (GCM) ECHAM5-HAM. The inclusion of bacteria acting as IN in a GCM leadsto only minor changes in cloud formation and precipitation on a global level, however,changes in the liquid water path and ice water path can be observed, specifically in theboreal regions where tundra and forests act as sources of bacteria. ISSN:1680-7375 ISSN:1680-7367